2014
DOI: 10.1038/nmat3945
|View full text |Cite
|
Sign up to set email alerts
|

Hippo/YAP-mediated rigidity-dependent motor neuron differentiation of human pluripotent stem cells

Abstract: Our understanding of the intrinsic mechanosensitive properties of human pluripotent stem cells (hPSCs), in particular the effects that the physical microenvironment has on their differentiation, remains elusive1. Here, we show that neural induction and caudalization of hPSCs can be accelerated by using a synthetic microengineered substrate system consisting of poly(dimethylsiloxane) micropost arrays (PMAs) with tunable mechanical rigidities. The purity and yield of functional motor neurons (MNs) derived from h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
247
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 245 publications
(264 citation statements)
references
References 30 publications
14
247
3
Order By: Relevance
“…YAP acts with TEAD transcription factors to drive cell cycle progression (18,19), and YAP depletion or inhibition of YAP-TEAD interactions can promote neuronal differentiation (19,20). Fu and coworkers (21) reported that polydimethylsiloxane micropost arrays that inhibit Hippo/YAP signaling can improve neuronal differentiation of hPS cells induced by soluble neurogenic factors. We postulated that the mechanical properties of the substrate alone would be powerful enough to poise cells for neuronal differentiation.…”
mentioning
confidence: 99%
“…YAP acts with TEAD transcription factors to drive cell cycle progression (18,19), and YAP depletion or inhibition of YAP-TEAD interactions can promote neuronal differentiation (19,20). Fu and coworkers (21) reported that polydimethylsiloxane micropost arrays that inhibit Hippo/YAP signaling can improve neuronal differentiation of hPS cells induced by soluble neurogenic factors. We postulated that the mechanical properties of the substrate alone would be powerful enough to poise cells for neuronal differentiation.…”
mentioning
confidence: 99%
“…A similar study has been performed in Caenorhabditis elegans zygotes in which actomyosin meshwork was ablated and the initial outward velocity of adjacent cortex was proportional to cortical tension (39). In separate studies, we know cytoskeleton tension is tightly connected to the Hippo-Yes-associated protein pathway that controls cell proliferation and organ growth (40)(41)(42). With the advance in genetically encoded, ratiometric biosensors for cell signaling proteins (43), there is some exciting potential in investigating how the distribution of tensile load by optical ablation could modulate spatial signaling.…”
Section: Optical Ablation Of Intracellular Structuresmentioning
confidence: 80%
“…However, coculturing different types of neural tissues is still difficult because culture conditions such as medium, growth factors, and extracellular matrix (ECM) differ according to the type of neural tissues. [27][28][29][30][31][32][33] Neurons also have the characteristic of axon overproduction and, consequently, axons extend over a wide area during early development. [34][35][36] Therefore, selective connectivity between specific, spatially separated neural tissues is technically difficult.…”
Section: Rod-shaped Neural Units For Aligned 3d Neural Network Connecmentioning
confidence: 99%
“…For example, differentiation induction of motor neurons from neural stem cells requires special medium conditions. [32] The composition of the culture medium and cell density is also different in cortical cells, [28] hippocampal cells, [29] and Purkinje cells of the cerebellar. [27,31] Using the proposed assembly of rodshaped neural units releases the construction of in vitro neural connective tissue from these culture condition limitations.…”
mentioning
confidence: 99%